OBSTACLES FACED BY ENGLISH COURSE TEACHERS IN IMPLEMENTING FORMATIVE ASSESSMENT - Warahmah, Mawaddah (Journal of Education and Teaching, 2023)
One type of assessment in EFL classroom that allows teachers to monitor students’ learning is formative assessment. However, conducting this assessment is not easy and straightforward so that there are some obstacles occurred during the implementation. This study is aimed to investigate the obstacles they faced by English course teachers in applying formative assessment. The data were collected by conducting interview with three English course teachers as the participants. The result showed that the participants had various obstacles in applying the assessment in the classroom such as those related with the topic raised for the assessment, the time used, and the honesty of students in receiving the formative assessment